MEMBACA “TINUNG” DALAM FILM CA BAU KAN: ANALISIS WACANA KRITIS DALAM PERSPEKTIF GENDER - Meutia, Fadhillah Sri (Jurnal Dakwah Tabligh, 2018)
This paper attempted to describe the representation of women in Ca Bau Kan through critical discourse analysis coined by Sara Mills in analyzing films using gender perspective. Theory of construction of reality by Berger and Luckmann was used to view how women are depicted in the film. Through gender perspective in media, this article reveals how film media constructs reality on women, who are associated with passiveness, obedience and dependence to men. It also discusses how the difference between masculinity and femininity is preserved by media culture. Lastly, this paper ends with a conclusion on the importance of equality between men and women so that film industry can represent women in the media better, provide gender perspective for the society, especially young Indonesian audience.